Diseminasi Efek Radiasi Speaker Aktif Di Lingkungan Sekolah Cengkareng - Simanjuntak, Imelda Uli Vistalina; Rahmawati, Yosy; Agustina, Ellisa; Salamah, Ketty Siti (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
Speakers are one of the standard electronic products with wireless capabilities. The Government of Indonesia is responsible for regulating and supervising the movement of goods using wireless domains through the Ministry of Communications and Information Technology. Electromagnetic compatibility (EMC) regulations are included in the entry requirements for wireless communication products to Indonesia. EMC means avoiding interference with other devices caused by radiation. Therefore, regarding this EMC regulation, it is necessary to pay attention to product quality and user safety. Through this community service program for the 2022 period, there will be the dissemination of the effects of active speaker radiation in the Cengkareng school environment as a preventive measure to minimize the impact of active speaker electronic emission radiation on the health of the academic community in the IP YAKIN Cengkareng Junior High School, Jakarta.